In memoriam: Carl J. Carrano - Frithjof C. Küpper; Eleanor Carrano; Kenneth N. Raymond; Eric Miller; Ricardo Cruz-López; Ana Mijovilovich; Kyoko Yarimizu; Andrew Cooksy; Wes Harris; Shady A. Amin; Alison Butler; John C. Carrano (BioMetals, 2026)
This article is a celebration of the life and work of Carl J. Carrano who, from a childhood in Long Island, New York, built a career in bioinorganic chemistry, especially in the context of metal uptake and halogen metabolism in microbes and marine organisms.

Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Precipitation variability interacts with mean precipitation to restructure a semiarid grassland community - Jennifer A. Rudgers; Laureano A. Gherardi; Purbendra Yogi; Melissa Bacigalupa; Tom E. X. Miller; Jacob J. Blais; Lana Bolin; Scott L. Collins; Enqing Hou; Yiqi Luo; Javier O. Morales; William T. Pockman; et al. (Ecology, 2026)
Climate forecasts project change not only in the mean of climate variables but also in their variance. If these dual changes interact, then future ecological dynamics will be difficult to predict using current experimental approaches, which typically change the mean or impose a single extreme event, such as drought. We designed a new field experiment to factorially reduce mean precipitation and increase its interannual variability. Across 4 years, drier, more variable precipitation additively reduced aboveground primary productivity by 48%–69% and interactively reduced the dominant plant species, but had no effect on the plant species predicted to dominate in the future, which could lead to state transition. Drier, more variable precipitation also interactively reduced biodiversity more than either climate factor alone, with 37%–42% fewer plant species than under ambient conditions, a pattern that matched declining richness during the past 20 years of ongoing climate change. Drier, more variable precipitation restructured the composition and spatiotemporal variation of the plant community. Altered precipitation mean or variance affected 14% of plant species, with eight species sensitive to the mean × variance interaction. Results suggest that future forecasts of plant community structure may be inadequate if they fail to incorporate climate mean × variance interactions.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Transformations of particulate organic matter from the surface to the abyssal plain in the North Pacific as inferred from compound-specific stable isotope and microbial community analyses - Lee C. Miller; Hilary G. Close; Kalina C. Grabb; Christine L. Huffard; Fuyan Li; David M. Karl; Kenneth L. Smith; Edward F. DeLong; Claudia R. Benitez-Nelson; Jeffrey C. Drazen; Brian N. Popp (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

The effect of enhanced glycolysis on cardiac aging - Anna Faakye; Kylene M. Harold; Satoshi Matsuzaki; Atul Pranay; Maria F. Mendez Garcia; Brooke L. Loveland; Sandra N. Rigsby; Frederick F. Peelor; Craig Eyster; Benjamin F. Miller; Timothy M. Griffin; Michael Kinter; et al. (GeroScience, 2025)
Cardiac aging is associated with metabolic changes, including an increased reliance on glycolysis, and an increased susceptibility to cardiovascular diseases. This study explores the relationship between enhanced cardiac glycolysis and aging using the Glyco Hi mouse model, characterized by constitutively elevated glycolysis. We compared cardiac function, metabolism, mitochondrial performance, and hallmarks of aging between aged (21 and 24 months) Glyco Hi and wild-type (WT) mice across sexes. Our findings reveal modest reductions in cardiac function in aged Glyco Hi mice compared to WT mice, with sex-specific differences in heart size and collagen concentration. Female Glyco Hi hearts exhibited hypertrophy without fibrosis, while males showed elevated collagen levels. Whole-body metabolic assessments revealed similar energy expenditure and respiratory patterns across genotypes, with females displaying less circadian-associated variation in metabolism. Mitochondrial analyses showed that aged Glyco Hi hearts maintained metabolic adaptations favoring glycolysis but did not exhibit significant bioenergetic dysfunction or oxidative stress. Pyruvate dehydrogenase activity, initially elevated in younger Glyco Hi hearts, normalized to WT levels with age. Proteomic and metabolomic analyses highlighted distinct profiles between genotypes, with Glyco Hi hearts exhibiting increased glycolytic enzyme levels and reduced abundance of fatty acid oxidation proteins. Despite these differences, indicators of oxidative stress, proteostasis, and cellular senescence were comparable between genotypes, suggesting no acceleration of aging-related dysfunction. This study demonstrates that increased cardiac glycolysis alone does not suffice to drive accelerated cardiac aging. Instead, metabolic and functional changes in aged Glyco Hi hearts reflect adaptations rather than pathological declines, providing insights into potential metabolic targets for interventions against cardiac aging.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Seasonally varying contributions of contemporaneous and lagged sources of instream total nitrogen and phosphorus load across the Illinois River basin - Noah M. Schmadel; Olivia L. Miller; Scott W. Ator; Matthew P. Miller; Gregory E. Schwarz; Dale M. Robertson; Andrew J. Sekellick; Kenneth D. Skinner; David A. Saad (Science of The Total Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Microbial symbionts buffer hosts from the demographic costs of environmental stochasticity - Joshua C. Fowler; Shaun Ziegler; Kenneth D. Whitney; Jennifer A. Rudgers; Tom E. X. Miller (Ecology Letters, 2024)
Species' persistence in increasingly variable climates will depend on resilience against the fitness costs of environmental stochasticity. Most organisms host microbiota that shield against stressors. Here, we test the hypothesis that, by limiting exposure to temporally variable stressors, microbial symbionts reduce hosts' demographic variance. We parameterized stochastic population models using data from a 14‐year symbiont‐removal experiment including seven grass species that host Epichloë fungal endophytes. Results provide novel evidence that symbiotic benefits arise not only through improved mean fitness, but also through dampened inter‐annual variance. Hosts with “fast” life‐history traits benefited most from symbiont‐mediated demographic buffering. Under current climate conditions, contributions of demographic buffering were modest compared to benefits to mean fitness. However, simulations of increased stochasticity amplified benefits of demographic buffering and made it the more important pathway of host–symbiont mutualism. Microbial‐mediated variance buffering is likely an important, yet cryptic, mechanism of resilience in an increasingly variable world.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Effect of degradation on geotechnical behavior of glauconite sands from the U.S. Mid-Atlantic Coastal Plain - Zachary J. Westgate; Don J. DeGroot; Christopher McMullin; Yuanjing Zou; Dongdong Guo; Simon Van Haren; Ryan D. Beemer; Danilo Zeppilli; Kenneth G. Miller; James V. Browning (Ocean Engineering, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Refinement of a microfurnace pyrolysis-GC–MS method for quantification of tire and road wear particles (TRWP) in sediment and solid matrices - Sharlee L. More; Julie V. Miller; Stephanie A. Thornton; Kathy Chan; Timothy R. Barber; Kenneth M. Unice (Science of The Total Environment, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

An Evaluation of Fish Tissue Monitoring Alternatives for Mercury and Selenium: Fish Muscle Biopsy Samples Versus Homogenized Whole Fillets - Leanne L. Stahl; Blaine D. Snyder; Harry B. McCarty; Tara R. Cohen; Kenneth M. Miller; Mark B. Fernandez; John C. Healey (Archives of Environmental Contamination and Toxicology, 2021)
Fish contaminant studies with human health protection objectives typically focus on muscle tissue, recognizing that fillets are the commonly consumed tissue fraction. Muscle biopsy punch sampling for mercury analysis has recently been used as an alternative to harvesting fish for fillets; however, there is limited information comparing fillet plug results to whole fillet results. This study was conducted to address that data gap and to test the applicability of plugs for monitoring associated with United States Environmental Protection Agency’s fish tissue-based mercury and selenium water quality criteria. The mercury phase included 300 fillet homogenates and 300 field-extracted plug samples from 60 fish, and the selenium phase included 120 fillet homogenates and 120 plugs from 30 fish. Both phases showed that there were no statistically significant differences between fillet plug and homogenized fillet results at the community level; however, a selenium plug monitoring alternative must employ a sufficiently sensitive analytical method and consider total solids. Plug and fillet sampling alternatives have inherent advantages and disadvantages. Fillet sampling provides sufficient mass to consider multiple contaminants but requires fish to be harvested. Plug sampling only provides adequate mass for a single analyte but may allow fish survival, although additional research is needed on survival following plug removal.

Spatial covariance of herbivorous and predatory guilds of forest canopy arthropods along a latitudinal gradient - Ondrej Mottl; Pavel Fibich; Petr Klimes; Martin Volf; Robert Tropek; Kristina Anderson‐Teixeira; John Auga; Thomas Blair; Phil Butterill; Grace Carscallen; Erika Gonzalez‐Akre; Aaron Goodman; et al. (Ecology Letters, 2020)
In arthropod community ecology, species richness studies tend to be prioritised over those investigating patterns of abundance. Consequently, the biotic and abiotic drivers of arboreal arthropod abundance are still relatively poorly known. In this cross‐continental study, we employ a theoretical framework in order to examine patterns of covariance among herbivorous and predatory arthropod guilds. Leaf‐chewing and leaf‐mining herbivores, and predatory ants and spiders, were censused on > 1000 trees in nine 0.1 ha forest plots. After controlling for tree size and season, we found no negative pairwise correlations between guild abundances per plot, suggestive of weak signals of both inter‐guild competition and top‐down regulation of herbivores by predators. Inter‐guild interaction strengths did not vary with mean annual temperature, thus opposing the hypothesis that biotic interactions intensify towards the equator. We find evidence for the bottom‐up limitation of arthropod abundances via resources and abiotic factors, rather than for competition and predation.

Ancient Sea Level as Key to the Future - Kenneth Miller; John Schmelz; James Browning; Robert Kopp; Gregory Mountain; James Wright (Oceanography, 2020)

Age matters: older age as a risk factor for CMV reactivation in the CMV serostatus–positive kidney transplant recipient - Marion Hemmersbach-Miller; Barbara D. Alexander; Carl F. Pieper; Kenneth E. Schmader (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Detailed characterization of repeat motifs of nine canid microsatellite loci in African painted dogs (Lycaon pictus) - Cassandra Miller-Butterworth; Karen Vacco; Kenneth Kaemmerer; Joseph Gaspard (Mammal Research, 2019)

Scientific Drilling Across the Shoreline - Sean Gulick; Kenneth Miller; Peter Keleman; Joanna Morgan; Jean-Noel Proust; Eiichi Takazawa (Oceanography, 2019)

Fifty Years of Scientific Ocean Drilling - Keir Becker; James Austin; Neville Exon; Susan Humphris; Miriam Kastner; Judith McKenzie; Kenneth Miller; Kiyoshi Suyehiro; Asahiko Taira (Oceanography, 2019)

Single-center analysis of infectious complications in older adults during the first year after kidney transplantation - Marion Hemmersbach-Miller; Barbara D. Alexander; Debra L. Sudan; Carl Pieper; Kenneth E. Schmader (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

How the Distribution of Anthropogenic Nitrogen Has Changed in Narragansett Bay (RI, USA) Following Major Reductions in Nutrient Loads - Autumn Oczkowski; Courtney Schmidt; Emily Santos; Kenneth Miller; Alana Hanson; Donald Cobb; Jason Krumholz; Adam Pimenta; Leanna Heffner; Sandra Robinson; Joaquín Chaves; Rick McKinney (Estuaries and Coasts, 2018)

Temperature sensitivity of nitrogen mineralization in agricultural soils - Kenneth S. Miller; Daniel Geisseler (Biology and Fertility of Soils, 2018)

Climatic variability of the Pacific and Atlantic Oceans and western US snowpack - Pratik Pathak; Ajay Kalra; Kenneth W. Lamb; William P. Miller; Sajjad Ahmad; Rajesh Amerineni; Devi P. Ponugoti (International Journal of Climatology, 2018)
This study examines the changing characteristics of snow water equivalent (SWE) in western United States and their teleconnections with large‐scale variability of the Pacific and Atlantic Oceans. This study evaluated the relationship among sea surface temperatures (SST), 500‐mbar geopotential height (Z 500 ), 500‐mbar east–west wind (U 500 ), and western United States SWE (1 March, 1 April, and 1 May). The averages of SST, Z 500 , and U 500 were computed to create a lead time of 2–10 months. Three different 6‐month series were computed – January–June, April–September, and July–December – and were correlated with SWE stations in the western United States. The study utilized singular‐value decomposition (SVD) for a period of 1961–2016 to correlate the SWE and climate indices. SVD was applied between the standardized SST and SWE to obtain their correlation and to evaluate connection with Z 500 and U 500 within the same SVD relationship. Specifically, SVD was not applied independently on each variable prior to this study. The correlations were observed to increase as the lead time decreased. First mode SVD showed a pronounced non‐El Niño‐Southern Oscillation short‐wave train for the July–December climate in the Z 500 data; this terminated over the Great Lakes region, and was strongly correlated with the warming of the SST near the east coast of Japan, resulting in decreased SWE in the study area. Second mode SVD showed a negative correlation between SWE stations in Colorado and Utah and SST near the Asian and Australian continents. The associations between climate indices and SWE that were identified during this study could be used to improve long‐term forecasts, resulting in better management of water resources in the region.

Modeling the Population Effects of Hypoxia on Atlantic Croaker (Micropogonias undulatus) in the Northwestern Gulf of Mexico: Part 2—Realistic Hypoxia and Eutrophication - Kenneth A. Rose; Sean Creekmore; Dubravko Justić; Peter Thomas; J. Kevin Craig; Rachael Miller Neilan; Lixia Wang; Md Saydur Rahman; David Kidwell (Estuaries and Coasts, 2018)

Modeling the Population Effects of Hypoxia on Atlantic Croaker (Micropogonias undulatus) in the Northwestern Gulf of Mexico: Part 1—Model Description and Idealized Hypoxia - Kenneth A. Rose; Sean Creekmore; Peter Thomas; J. Kevin Craig; Md Saydur Rahman; Rachael Miller Neilan (Estuaries and Coasts, 2018)

An oral form of methylglyoxal-bis-guanylhydrazone reduces monocyte activation and traffic to the dorsal root ganglia in a primate model of HIV-peripheral neuropathy - Jessica R. Lakritz; Samshita Yalamanchili; Michael J. Polydefkis; Andrew D. Miller; Michael S. McGrath; Kenneth C. Williams; Tricia H. Burdo (Journal of NeuroVirology, 2017)

Comparing Measures of Estuarine Ecosystem Production in a Temperate New England Estuary - Autumn Oczkowski; Christopher W. Hunt; Kenneth Miller; Candace Oviatt; Scott Nixon; Leslie Smith (Estuaries and Coasts, 2016)

Nitrogen Retention in Salt Marsh Systems Across Nutrient-Enrichment, Elevation, and Precipitation Regimes: a Multiple-Stressor Experiment - Autumn Oczkowski; Cathleen Wigand; Alana Hanson; Erin Markham; Kenneth M. Miller; Roxanne Johnson (Estuaries and Coasts, 2016)

Erratum to: Influence of Location, Year, Potato Rotation, and Chemical Seed Treatment on Incidence and Severity of Silver Scurf on Progeny Tubers - Jeffrey S. Miller; Philip B. Hamm; Jeremiah K. S. Dung; Brad D. Geary; Steven R. James; Dennis A. Johnson; Kenneth Rykbost (American Journal of Potato Research, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

Influence of Location, Year, Potato Rotation, and Chemical Seed Treatment on Incidence and Severity of Silver Scurf on Progeny Tubers - Jeffrey S. Miller; Philip B. Hamm; Jeremiah K. S. Dung; Brad D. Geary; Steven R. James; Dennis A. Johnson; Kenneth Rykbost (American Journal of Potato Research, 2015)

Diabetes and colorectal cancer screening among men and women in the USA: National Health Interview Survey: 2008, 2010 - Eric A. Miller; Yelena N. Tarasenko; Jennifer D. Parker; Kenneth C. Schoendorf (Cancer Causes & Control, 2014)

Erratum to: Status and access to the Collaborative Cross population - Catherine E. Welsh; Darla R. Miller; Kenneth F. Manly; Jeremy Wang; Leonard McMillan; Grant Morahan; Richard Mott; Fuad A. Iraqi; David W. Threadgill; Fernando Pardo-Manuel de Villena (Mammalian Genome, 2014)

Influence of tidal‐range change and sediment compaction on Holocene relative sea‐level change in New Jersey, USA - BENJAMIN P. HORTON; SIMON E. ENGELHART; DAVID F. HILL; ANDREW C. KEMP; DARIA NIKITINA; KENNETH G. MILLER; W. RICHARD PELTIER (Journal of Quaternary Science, 2013)
We investigated the effect of tidal‐range change and sediment compaction on reconstructions of Holocene relative sea level (RSL) in New Jersey, USA. We updated a published sea‐level database to generate 50 sea‐level index points and ten limiting dates that define continuously rising RSL in New Jersey during the Holocene. There is scatter among the index points, particularly those older than 7 ka. A numerical model estimated that paleotidal range was relatively constant during the mid and late Holocene, but rapidly increased between 9 and 8 ka, leading to an underestimation of RSL by ∼0.5 m. We adjusted the sea‐level index points using the paleotidal model prior to assessing the influence of compaction on organic samples with clastic deposits above and below (an intercalated sea‐level index point). We found a significant relationship ( p = 0.01) with the thickness of the overburden ( r = 0.85). We altered the altitude of intercalated index points using this simple stratigraphic relationship, which reduced vertical scatter in sea‐level reconstructions. We conclude that RSL rose at an average rate of 4 mm a −1 from 10 ka to 6 ka, 2 mm a −1 from 6 ka to 2 ka, and 1.3 mm a −1 from 2 ka to AD 1900. Copyright © 2013 John Wiley & Sons, Ltd.

Status and access to the Collaborative Cross population - Catherine E. Welsh; Darla R. Miller; Kenneth F. Manly; Jeremy Wang; Leonard McMillan; Grant Morahan; Richard Mott; Fuad A. Iraqi; David W. Threadgill; Fernando Pardo-Manuel de Villena (Mammalian Genome, 2012)

Compositional gradients surrounding spherulites in obsidian and their relationship to spherulite growth and lava cooling - James E. Gardner; Kenneth S. Befus; James Watkins; Marc Hesse; Nathan Miller (Bulletin of Volcanology, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

A 180-Million-Year Record of Sea Level and Ice Volume Variations from Continental Margin and Deep-Sea Isotopic Records - Kenneth Miller; Gregory Mountain; James Wright; James Browning (Oceanography, 2011)

Impacts of Oyster Reef Restoration on Primary Productivity and Nutrient Dynamics in Tidal Creeks of the North Central Gulf of Mexico - Rochelle Plutchak; Kelly Major; Just Cebrian; C. Drew Foster; Mary-Elizabeth C. Miller; Andrea Anton; Kate L. Sheehan; Kenneth L. Heck; Sean P. Powers (Estuaries and Coasts, 2010)

The impact of Hurricane Ivan on the primary productivity and metabolism of marsh tidal creeks in the NorthCentral Gulf of Mexico - Just Cebrian; C. Drew Foster; Rochelle Plutchak; Kate L. Sheehan; Mary-Elizabeth C. Miller; Andrea Anton; Kelly Major; Kenneth L. Heck; Sean P. Powers (Aquatic Ecology, 2008)

The Collaborative Cross at Oak Ridge National Laboratory: developing a powerful resource for systems genetics - Elissa J. Chesler; Darla R. Miller; Lisa R. Branstetter; Leslie D. Galloway; Barbara L. Jackson; Vivek M. Philip; Brynn H. Voy; Cymbeline T. Culiat; David W. Threadgill; Robert W. Williams; Gary A. Churchill; Dabney K. Johnson; et al. (Mammalian Genome, 2008)

Cancer incidence and mortality patterns among specific Asian and Pacific Islander populations in the U.S. - Barry A. Miller; Kenneth C. Chu; Benjamin F. Hankey; Lynn A. G. Ries (Cancer Causes & Control, 2008)

Cancer incidence and mortality patterns among specific Asian and Pacific Islander populations in the U.S. - Barry A. Miller; Kenneth C. Chu; Benjamin F. Hankey; Lynn A. G. Ries (Cancer Causes & Control, 2008)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Increased extracellular glutamate evoked by 1-Methyl-4-phenylpyridinium (MPP+) in the rat striatum is not essential for dopaminergic neurotoxicity and is not derived from released glutathione - Steven B. Foster; Haiwang Tang; Kenneth E. Miller; Glenn Dryhurst (Neurotoxicity Research, 2005)

Dormant Season Prescribed Fire as a Management Tool for the Control of Salix caroliniana Michx. in a Floodplain Marsh - Mary Ann B. Lee; Kenneth L. Snyder; Patricia Valentine-Darby; Steven J. Miller; Kimberli J. Ponzio (Wetlands Ecology and Management, 2005)

How Modeling and Simulation Have Enhanced Decision Making in New Drug Development - Raymond Miller; Wayne Ewy; Brian W. Corrigan; Daniele Ouellet; David Hermann; Kenneth G. Kowalski; Peter Lockwood; Jeffrey R. Koup; Sean Donevan; Ayman El-Kattan; Cheryl SW Li; John L. Werth; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2005)

Early Prediction of Pharmaceutical Oxidation Pathways by Computational Chemistry and Forced Degradation - Darren L. Reid; C. Jeffrey Calvitt; Mark T. Zell; Kenneth G. Miller; Carol A. Kingsmill (Pharmaceutical Research, 2004)

A Two-Part Mixture Model for Longitudinal Adverse Event Severity Data - Kenneth G. Kowalski; Lynn McFadyen; Matthew M. Hutmacher; Bill Frame; Raymond Miller (Journal of Pharmacokinetics and Pharmacodynamics, 2003)

Mitogen activated protein kinase pathway is involved in RhoC GTPase induced motility, invasion and angiogenesis in inflammatory breast cancer - Kenneth L. van Golen; Li Wei Bao; Quintin Pan; Fred R. Miller; Zhi Fen Wu; Sofia D. Merajver (Clinical & Experimental Metastasis, 2002)

Nigrostriatal dopaminergic neurotoxicity of L-cysteine after stereotaxic administration into the substantia nigra of rats: Potential implications for MPTP-induced neurotoxicity and parkinson’s disease - Lihong Gu; Kenneth E. Miller; Glenn Dryhurst (Neurotoxicity Research, 2000)

Nerve growth factor-induced stimulation of dorsal root ganglion/spinal cord co-grafts in oculo: enhanced survival and growth of CGRP-immunoreactive sensory neurons - Kenneth E. Miller; Elisabet Åkesson; Åke Seiger (Cell and Tissue Research, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The genetics and expression of an esterase locus inAnopheles gambiae - Kenneth D. Vernick; Frank H. Collins; Douglas C. Seeley; Robert W. Gwadz; Louis H. Miller (Biochemical Genetics, 1988)

The genetics and expression of an esterase locus inAnopheles gambiae - Kenneth D. Vernick; Frank H. Collins; Douglas C. Seeley; Robert W. Gwadz; Louis H. Miller (Biochemical Genetics, 1988)

Heliobacterium chlorum: cell organization and structure - Kenneth R. Miller; Jules S. Jacob; Ursula Smith; Stephen Kolaczkowski; Michael K. Bowman (Archives of Microbiology, 1986)

The Rhodopseudomonas viridis photosynthetic membrane: arrangement in situ - Kenneth R. Miller; Jules S. Jacob (Archives of Microbiology, 1985)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)